If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 = 44 + -3x Reorder the terms: 9 + 3x = 44 + -3x Solving 9 + 3x = 44 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 9 + 3x + 3x = 44 + -3x + 3x Combine like terms: 3x + 3x = 6x 9 + 6x = 44 + -3x + 3x Combine like terms: -3x + 3x = 0 9 + 6x = 44 + 0 9 + 6x = 44 Add '-9' to each side of the equation. 9 + -9 + 6x = 44 + -9 Combine like terms: 9 + -9 = 0 0 + 6x = 44 + -9 6x = 44 + -9 Combine like terms: 44 + -9 = 35 6x = 35 Divide each side by '6'. x = 5.833333333 Simplifying x = 5.833333333
| 29+n=-(-5n-5) | | 7(2+w)=6(w-9) | | 6=2+u | | 2(2x-6)m+2(x+3)m=26 | | 4n^2+9n+5= | | 5(2x-3)=x+3 | | 13x-8+2x-5=12x-2+2x | | -16=22 | | 7p+3+4p+5= | | 17=4(x+5)-5x | | 8y=y-56 | | .2d=-3 | | -5t+t+(-12t)= | | 328=2(8-w) | | 172=2x+4(6x+4) | | 4v^2-12v^2-5v+15=0 | | .20x+.92*10=.65(x+10) | | .75*.75-6= | | 7a^2+22a+3= | | -k=(k-10) | | 2x-6=6-2x | | 36x=81 | | x+21=-8 | | 16=v(v-6) | | 9x-20+6x-5=180 | | 41=-r+32 | | 2x^2-5x-12= | | 9x(4)=81 | | 9x(4)= | | 8T=-4 | | 7x+9=6x+20 | | 3.33x=30 |